2014
DOI: 10.1088/0953-2048/27/12/125004
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of the gap parameter in the hole-doped cuprates

Abstract: The structure of the gap parameter (∆ k ) for the hole-doped cuprates has been studied. The obtained results indicate that the antinodal part of ∆ k is very weakly temperature dependent and above the critical temperature (TC), it extends into the anomalous normal state to the pseudogap temperature. On the other hand, the values of ∆ k , which are close to the nodal part, are strongly temperature dependent. The model has been tested for the YBa2Cu3O 7−δ superconductor. It has been shown that the theoretical res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 61 publications
1
44
0
Order By: Relevance
“…In order to determine precisely the physical value of the energy gap at the Fermi level, and supplement results obtained in the previous section, the Eliashberg equations are solved in the mixed representation (for more details please see [26], [37] and [38]). This procedure allows to obtain the solutions of the Eliashberg equations on the real axis (ω), which provide the quantitative values of the energy gap at the Fermi level (2∆(T )) from:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to determine precisely the physical value of the energy gap at the Fermi level, and supplement results obtained in the previous section, the Eliashberg equations are solved in the mixed representation (for more details please see [26], [37] and [38]). This procedure allows to obtain the solutions of the Eliashberg equations on the real axis (ω), which provide the quantitative values of the energy gap at the Fermi level (2∆(T )) from:…”
Section: Resultsmentioning
confidence: 99%
“…This is a general trend in the domain of superconductivity which aims to achieve the highest possible value of critical temperature (T C ) in the given material (please see for example [30], [31], [32]). In particular, proposition given in [29] should be of crucial interest for the scientific community, since bilayer lithium-decorated graphene structures are already experimentally proved to be thermodynamically stable [33].…”
Section: Introductionmentioning
confidence: 99%
“…Wherein the measured critical temperature (T C ) of 203 K in hydrogen sulfide is among the highest over allknown superconductors [5]. The theoretical studies have revealed a significantly more superconducting hydrogenrich materials such as PtH [7,8], H 2 S [9], GaH 3 [10,11], ScH 3 [12,13], SnH 4 [14], GeH 4 [15,16], NbH 4 [17,18], CaH 6 [19], MgH 6 [20] of which the highest critical temperature equal to 263−271 K was estimated for MgH 6 compound at a pressure range from 300 to 400 GPa [20]. As it turns out pressure (p) can have a very large impact on the critical temperature and thermodynamics of superconducting state.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in the family of hydrogenated silicon: Si 2 H 6 at 275 GPa and SiH 4 (H 2 ) 2 at 250 GPa, application of the Allen-Dynes modified McMillan equation gives the highest superconducting transition temperatures amounts 153 K and 107 K, respectively [13,14]. In hydrogenated germane GeH 4 (H 2 ) 2 at 250 GPa, T C is equals to 90 K [15] and hydrogenated gallane GaH 3 at 120 GPa is characterized by T C = 102 K [16] (T C rises to 123 K when calculations are conducted in the framework of the Eliashberg formalism [17]). …”
Section: Introductionmentioning
confidence: 99%
“…A proper treatment of those effects was developed in Eliashberg theory which allows to reproduce the superconducting properties of a conventional superconductor within an experimental accuracy. This approach has been described in paper [24] and successfully used in the study of other hydrogen-rich compounds [17,19,25], and also in the study of materials for which is a possibility of comparison of the theoretical and experimental results (e.g. simple elements: Ca, S, Li, and compounds: CaLi 2 , K 3 C 60 , Rb 3 C 60 , MgB 2 ) [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%